Global, regional, and national burden of IHD attributable to PM pollution aged 70 and above: an age-period-cohort modeling and frontiers analysis study - He, Ke-Jie; Wang, Haitao; Liu, Xu; Yang, Rongying; Gong, Guoyu (Frontiers in Public Health, 2025)
BackgroundParticulate matter (PM) pollution is a significant risk factor for ischemic heart disease (IHD). This study evaluates the global, regional, and national burden of IHD attributable to PM pollution from 1990 to 2021, quantifies key contributing factors, and projects trends to 2044, with a focus on regional disparities and population aging.MethodsUsing data from the Global Burden of Disease (GBD) 2021 study, we analyzed trends in IHD-related disability-adjusted life years (DALYs) and mortality attributable to PM pollution. Joinpoint regression assessed long-term trends, Age-Period-Cohort modeling evaluated demographic drivers, and decomposition analysis identified the contributions of population growth, aging, and epidemiological changes. Frontier analysis compared observed DALY rates with the lowest achievable rates based on socio-demographic index (SDI). Future trends were projected using the Nordpred model.ResultsFrom 1990 to 2021, global age-standardized DALY rates for IHD attributable to PM pollution decreased by −1.51% annually, but absolute DALYs increased due to population aging and growth. High SDI regions saw significant declines in DALY rates (−4.75% annually), while Low SDI regions experienced negligible change (0.01%). Population growth contributed to a 183.57% increase in global DALYs, but epidemiological improvements reduced the burden by 89.29%. Frontier analysis revealed substantial unrealized potential for reducing the IHD burden, particularly in Middle SDI regions. Projections to 2044 indicate that while DALY rates will decline, total DALYs will increase among individuals aged over 70, especially in Low and Low-middle SDI regions.ConclusionsThis study highlights substantial progress in reducing the IHD burden attributable to PM pollution, particularly in High SDI regions. However, disparities remain, especially in Low and Low-middle SDI regions, where the aging population and insufficient healthcare infrastructure exacerbate the burden. The rising IHD burden among the older adult underscores the need for targeted interventions, including stricter air quality regulations, enhanced healthcare access, and policies that specifically address vulnerable populations. Strengthening healthcare systems and air pollution controls in these regions is critical to mitigating the growing IHD burden in the coming decades.